The Effectiveness of The Learning Model of Probelem Based Learning on The Learning Outcomes of Bottom Passing - Yudha Caksana, Krisia; Fahmi, Donny Anhar; Kresnapati, Pandu (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The background of this study is the lack of understanding of students about the basic techniques of volleyball, one of them is about the bottom passing. In the learning process. The teacher always gives conventional learning model. It is like only give instruction so it makes the students less enthusiastic in participating in learning. So, the students just reach the learning value of volleyball bottom passing which is still much below the KKM (70), which is 12 students while those above the KKM (75) or complete A total of 15 students. The purpose of this study is to determine the effectiveness of the problem-based learning model on the learning outcomes of volleyball bottom passing game in grade IV students of SDN 2 Sendangharjo. The type of research used by the researcher in this research is quantitative using a one group pre-test - post-test design. The Population is a fourth grade student of SDN 2 Sendangharjo. with the method of taking saturated samples (all populations are made into samples), which is 23 students. The instrument used in this study is a volleyball bottom test pass. Data calculations are assisted by using Microsoft exel.The results of the study using problem-based learning model in learning to pass bottom the volleyball game increased by 30.43%. From the results of the study, it was explained that the learning method given to each group had an effect from the initial data of complete student data was only 34.78%,  65.22% of incomplete students and  the pre-test showed it increased to 60.87% for students who complete. The student who have not completed are 39.13. Meanwhile, in the post-test is 91.30 for students who are in the complete category, while those who have not completed it are 8.70%. The increase can be seen from the results of the pretest of 60.87% to the posttest of 91.30%. The conclusion of this study is that the problem-based learning model is effectively used to improve the learning of passing under the volleyball game in students. The presentation, the learning outcome increased by 30.43%. The suggestion from the researcher to the next researcher is to be able to develop a problem-based learning model to improve the learning of other PJOK materials.